Social dialogue through the rationalisation and redeployment policy process in education post 1994 : an analysis of perceptions and experiences of key policy actors within the Gauteng province.' - Clark, Colette Bronwen (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2003.